The association between time of in hospital cardiac arrest and mortality; a retrospective analysis of two UK databases. (May 2023) - McGuigan, Peter J; Edwards, Julia; Blackwood, Bronagh; Dark, Paul; Doidge, James C.; Harrison, David A.; Kitchen, Gareth; Lawson, Izabella; Nichol, Alistair D.; Rowan, Kathryn M.; Shankar-Hari, Manu; McAuley, Danny F
Abstract: Aims: The incidence of in hospital cardiac arrest (IHCA) varies throughout the day. This study aimed to report the variation in incidence of IHCA, presenting rhythm and outcome based on the hour in which IHCA occurred. Methods: We conducted a retrospective analysis of the National Cardiac Arrest Audit (NCAA) including patients who suffered an IHCA from 1st April 2011 to 31st December 2019. We then linked the NCAA and intensive care Case Mix Programme databases to explore the effect of time of IHCA on hospital survival in the subgroup of patients admitted to intensive care following IHCA. Results: We identified 115, 690 eligible patients in the NCAA database. Pulseless electrical activity was the commonest presenting rhythm (54.8%). 66, 885 patients died in the immediate post resuscitation period. Overall, hospital survival in the NCAA cohort was 21.3%. We identified 13, 858 patients with linked ICU admissions in the Case Mix Programme database; 37.0% survived to hospital discharge. The incidence of IHCA peaked at 06.00. Rates of return of spontaneous circulation, survival to hospital discharge and good neurological outcome were lowest between 05.00 and 07.00. Among those admitted to ICU, no clear diurnal variation in hospital survival was seen in the unadjusted or adjusted analysis. This pattern was consistent across all presenting rhythms. Conclusions: We observed higher rates of IHCA, and poorer outcomes at night. However, in those admitted to ICU, this variation was absent. This suggests patient factors and processes of care issues contribute to the variation in IHCA seen throughout the day.